Benchmarking the Extent and Speed of Reperfusion: First Pass TICI 2c-3 Is a Preferred Endovascular Reperfusion Endpoint - Yoo, Albert J.; Soomro, Jazba; Andersson, Tommy; Saver, Jeffrey L.; Ribo, Marc; Bozorgchami, Hormozd; Dabus, Guilherme; Liebeskind, David S.; Jadhav, Ashutosh; Mattle, Heinrich; Zaidat, Osama O. (Frontiers in Neurology, 2021)
Background and Purpose End-of-procedure substantial reperfusion (modified Treatment in Cerebral Ischemia [mTICI] 2b-3), the leading endpoint for thrombectomy studies, has several limitations including a ceiling effect, with recent achieved rates of ~90%. We aimed to identify a more optimal definition of angiographic success along two dimensions: 1) the extent of tissue reperfusion, and 2) the speed of revascularization. Methods Core-lab adjudicated TICI scores for the first three passes of EmboTrap and the final all-procedures result were analyzed in the ARISE II multicenter study. The clinical impact of extent of reperfusion and speed of reperfusion (first-pass vs. later-pass) were evaluated. Clinical outcomes included 90-day functional independence (modified Rankin Scale [mRS] 0-2), 90-day freedom-from-disability (mRS 0-1), and dramatic early improvement (24-hour National Institutes of Health Stroke Scale [NIHSS] improvement ≥8 points). Results Among 161 ARISE II subjects with ICA or MCA M1 occlusions, reperfusion results at procedure end showed substantial reperfusion in 149 (92.5%), excellent reperfusion in 121 (75.2%), and complete reperfusion in 79 (49.1%). Reperfusion rates on first pass were substantial in 81 (50.3%), excellent reperfusion in 62 (38.5%), and complete reperfusion in 44 (27.3%). First-pass excellent reperfusion (first-pass TICI 2c-3) had the greatest nominal predictive value for 90-day mRS 0-2 (sensitivity 58.5%, specificity 68.6%). There was a progressive worsening of outcomes with each additional pass required to achieve TICI 2c-3. Conclusions First-pass excellent reperfusion (TICI 2c-3), reflecting rapid achievement of extensive reperfusion, is the technical revascularization endpoint that best predicted functional independence in this international multicenter trial and is an attractive candidate for a lead angiographic endpoint for future trials.